2009
DOI: 10.5194/bg-6-515-2009
|View full text |Cite
|
Sign up to set email alerts
|

Imminent ocean acidification in the Arctic projected with the NCAR global coupled carbon cycle-climate model

Abstract: Abstract. Ocean acidification from the uptake of anthropogenic carbon is simulated for the industrial period and IPCC SRES emission scenarios A2 and B1 with a global coupled carbon cycle-climate model. Earlier studies identified seawater saturation state with respect to aragonite, a mineral phase of calcium carbonate, as a key variable governing impacts on corals and other shell-forming organisms. Globally in the A2 scenario, water saturated by more than 300%, considered suitable for coral growth, vanishes by … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

22
463
5
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 457 publications
(492 citation statements)
references
References 58 publications
22
463
5
2
Order By: Relevance
“…Even though globally-averaged ! arag values in surface waters remain above unity for a doubling of atmospheric CO 2 , large parts of the Southern Ocean and the Arctic Ocean are projected to become undersaturated with respect to aragonite as early as 2030-2060 (Orr et al 2005;McNeil and Matear 2008;Steinacher et al, 2009). Aragonite undersaturation means that these waters will become corrosive to the aragonite and high-magnesium calcite shells secreted by a wide variety of marine organisms.…”
Section: Ocean Acidificationmentioning
confidence: 99%
“…Even though globally-averaged ! arag values in surface waters remain above unity for a doubling of atmospheric CO 2 , large parts of the Southern Ocean and the Arctic Ocean are projected to become undersaturated with respect to aragonite as early as 2030-2060 (Orr et al 2005;McNeil and Matear 2008;Steinacher et al, 2009). Aragonite undersaturation means that these waters will become corrosive to the aragonite and high-magnesium calcite shells secreted by a wide variety of marine organisms.…”
Section: Ocean Acidificationmentioning
confidence: 99%
“…Such a strategy could be used to complement (not replace) direct observations of pH, TCO 2 , and TA. Predictions of pH e and W arag e could also be used as a tool to evaluate global coupled model simulations of ocean carbon chemistry [Orr et al, 2005;Steinacher et al, 2009], identify regional vulnerabilities to ocean carbon chemistry given understanding of critical life history stages (spawning, juvenile development), and hindcast conditions for recent biological or ecological datasets for which concurrent pH, TCO 2 , and TA observations are unavailable.…”
Section: Discussionmentioning
confidence: 99%
“…According to their model, decreased sea ice extent leads to greater atmosphere-ocean exchange of CO 2 , which in turn drives an accelerated decline for both pH and saturation states. Steinacher et al [2009], in a separate model study, demonstrated that the largest pH changes will occur in Arctic Ocean surface waters, where aragonite undersaturation is projected within a decade due to freshening by precipitation and ice melt and by increased carbon uptake as the ice cover is reduced.…”
Section: Introductionmentioning
confidence: 99%
“…Rapidly changing conditions in the Arctic, such as altered hydrological cycles, rising seawater temperature and reduction of ice cover, impact biogeochemical cycles [Arrigo et al, 2008]. Anticipated changes in saturation states in the Arctic surface waters [Steinacher et al, 2009] will propagate downstream through the CAA southward from the Labrador Shelf to the Middle Atlantic Bight. We report the current calcite and aragonite saturation states of seawater and the depths of saturation horizons based on dissolved inorganic carbon and total alkalinity measurements from the CAA and the Labrador Sea in [2003][2004][2005].…”
Section: Introductionmentioning
confidence: 99%